Twentieth-century English Bible translations - Naudé, J. A. (Acta Theologica, 2005)
The twentieth century has emerged as a major period of Bible translations and publications. The article explores both the cultural and social circumstances under which the English Bible translations of the twentieth century were produced and aspects relating to the translation process and reception. It offers insights into the underlying objectives and qualities of translations as well as the tradition from which they stem. The primary concern for meaning and readability has influenced the nature of Bible translation of this period, breaking down the socio-cultural distance between modern readers and the original contexts of the Bible.